EVALUATING THE EFFECTIVENESS OF PBL IN ENHANCING SPEAKING SKILLS IN NON-FORMAL EDUCATION - Saripi, Samid; Asari, Slamet (University of Kuningan, 2024)
This study examines the impact of Project-Based Learning (PBL) on enhancing speaking skills among Paket C students at Pusat Kegiatan Belajar Masyarakat (PKBM) Husnan Limboto, a non-formal educational institution in Indonesia. The research adopts a mixed-methods approach, integrating both qualitative and quantitative methods to evaluate the effectiveness of Project-Based Learning (PBL) in enhancing speaking skills in non-formal education settings. This approach ensures a comprehensive understanding of the phenomena by combining numerical data with contextual insights, the study developed and evaluated PBL materials aimed at improving fluency, coherence, and pronunciation. A mixed-methods approach was employed, combining quantitative assessments with qualitative feedback from students and teachers. The results showed significant improvements in students' speaking proficiency, with fluency increasing from a mean score of 3.2 to 4.5 (a 40.6% improvement), coherence rising from 3.0 to 4.3 (43.3% increase), and pronunciation improving from 2.8 to 4.1 (46.4% increase). Student motivation and engagement also saw considerable gains, with motivation scores increasing from 3.1 to 4.6 (48.4%) and engagement from 3.0 to 4.7 (56.7%). These improvements underscore the effectiveness of PBL in fostering speaking skills in a non-formal education setting. However, the study also highlights challenges such as insufficient technological resources and the need for professional development for teachers to fully implement PBL. Recommendations include addressing infrastructure issues, providing more training for educators, and developing cost-effective PBL models for resource-limited environments. Future research should explore the long-term impact of PBL on students' academic and professional success.